Discovery of novel non-steroidal reverse indole mineralocorticoid receptor antagonists. Issue 12 (15th June 2016) - Ogawa, Anthony K.; Bunte, Ellen Vande; Mal, Rudrajit; Lan, Ping; Sun, Zhongxiang; Crespo, Alejandro; Wiltsie, Judyann; Clemas, Joseph; Gibson, Jack; Contino, Lisa; Lisnock, JeanMarie; Zhou, Gaochao; et al.
Graphical abstract: Reported herein are a series of reverse indoles that represent novel non-steroidal mineralocorticoid receptor (MR) antagonists. The key structure–activity relationships (SAR) and acute pharmacodynamic efficacy in an acute natriuresis rodent model are presented. Abstract: Reported herein are a series of reverse indoles that represent novel non-steroidal mineralocorticoid receptor (MR) antagonists. The key structure–activity relationships (SAR) are presented below. This reverse indole series is exemplified by a compound that demonstrated efficacy in an acute natriuresis rodent model comparable to marketed MR antagonists, spironolactone and eplerenone.